2022
DOI: 10.1016/j.cell.2021.12.032
|View full text |Cite
|
Sign up to set email alerts
|

The Omicron variant is highly resistant against antibody-mediated neutralization: Implications for control of the COVID-19 pandemic

Abstract: The rapid spread of the SARS-CoV-2 Omicron variant suggests that the virus might become globally dominant. Further, the high number of mutations in the viral spike-protein raised concerns that the virus might evade antibodies induced by infection or vaccination. Here, we report that the Omicron spike was resistant against most therapeutic antibodies but remained susceptible to inhibition by Sotrovimab. Similarly, the Omicron spike evaded neutralization by antibodies from convalescent or BNT162b2-vaccinated ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

52
727
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(782 citation statements)
references
References 65 publications
52
727
1
2
Order By: Relevance
“…25 There is thus great concern about the Omicron variant's higher transmissibility and immune escapes from COVID-19 vaccines and antibody-based therapies. [26][27][28][29] It has also been demonstrated that vaccine-induced neutralizing antibody responses decrease with increased time post-vaccination. 30,31 To counteract the decline of the neutralizing antibody response over time and the emergence of new variants including Omicron, a third dose of vaccination, which has been called a "booster vaccination," has been approved and administered to individuals who were vaccinated >6 months ago; the booster vaccination has been shown to 6 effectively induce a high titer of neutralizing antibody.…”
Section: Introductionmentioning
confidence: 99%
“…25 There is thus great concern about the Omicron variant's higher transmissibility and immune escapes from COVID-19 vaccines and antibody-based therapies. [26][27][28][29] It has also been demonstrated that vaccine-induced neutralizing antibody responses decrease with increased time post-vaccination. 30,31 To counteract the decline of the neutralizing antibody response over time and the emergence of new variants including Omicron, a third dose of vaccination, which has been called a "booster vaccination," has been approved and administered to individuals who were vaccinated >6 months ago; the booster vaccination has been shown to 6 effectively induce a high titer of neutralizing antibody.…”
Section: Introductionmentioning
confidence: 99%
“…While for Delta S trimer, our recent work showed the open-transition ratio is 75.3%-24.7%, indicating the conformational masking mechanism may be less effective for the Delta variant 32,36 . This could contribute greatly to the striking immune evasion of the Omicron variant 15,[17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…As the consequence, Omicron has been observed to extensively escape neutralization by previously developed neutralizing monoclonal antibodies (MAbs) or sera from vaccines or convalescent individuals 15,[17][18][19][20][21][22] . Among all of the Omicron S mutations, 15 are present in the receptor-binding domain (RBD) that mediates the virus binding to its host-cell receptorangiotensin-converting enzyme 2 (ACE2) and is also a major target for neutralizing antibodies [23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory studies and epidemiological reports have now confirmed this exceptional combination of high contagiousity and drastic escape from neutralizing antibodies [ 10 12 ]. The resistance to neutralization is most likely due to mutations K417N, N440K, G446S, S477N, T478K, E484A, Q493R, G496S, Q498R, N501Y and Y505H, which are located within or close to the epitopes bound by these antibodies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%